2018
DOI: 10.1002/hed.25376
|View full text |Cite|
|
Sign up to set email alerts
|

Response of head and neck epithelial cells to a DNA damage‐differentiation checkpoint involving polyploidization

Abstract: Background Squamous epithelia of the head and neck undergo continuous cell renewal and are continuously exposed to mutagenic hazard, the main cause of cancer. How they maintain homeostasis upon cell cycle deregulation is unclear. Methods To elucidate how head and neck epithelia respond to cell cycle stress, we studied human keratinocytes from various locations (oral mucosa, tonsil, pharynx, larynx, and trachea). We made use of genotoxic or mitotic drugs (doxorubicin [DOXO], paclitaxel, and nocodazole), or chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…A differentiation response to DNA damage might be essential in tissues exposed to genetic insult that fulfil a specialised function, where apoptosis would be deleterious. It is interesting that deregulation of the keratinocyte cell cycle by overexpression of MYC, Cyclin E or inactivation of p53 causes DNA damage, mitotic slippage and terminal differentiation [5,6,8]. Our results now provide mechanisms for the prevailing keratinocyte differentiation fate in response to genetic damage.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A differentiation response to DNA damage might be essential in tissues exposed to genetic insult that fulfil a specialised function, where apoptosis would be deleterious. It is interesting that deregulation of the keratinocyte cell cycle by overexpression of MYC, Cyclin E or inactivation of p53 causes DNA damage, mitotic slippage and terminal differentiation [5,6,8]. Our results now provide mechanisms for the prevailing keratinocyte differentiation fate in response to genetic damage.…”
Section: Discussionmentioning
confidence: 68%
“…We have found a cell-autonomous mechanism that triggers differentiation in response to cell cycle stress in human primary keratinocytes in vitro [ 4 6 ]. DNA damage caused by genotoxic agents (chemicals, UV irradiation) [ 6 8 ] or oncogenic replication stress, induces squamous differentiation. This differentiation response is triggered via mitotic checkpoints and involves cytokinesis failure and endoreplication.…”
Section: Introductionmentioning
confidence: 99%
“…However, older reports showing frequent mitotic figures in suprabasal layers of the skin and various other observations suggested otherwise (reviewed in [1]). We have obtained a large body of evidence for a role of mitotic checkpoints in squamous differentiation [2][3][4][5]. Our studies consistently showed that after a sustained block of mitosis keratinocytes undergo mitotic slippage or mitotic bypass, continue DNA replication and become tetraploid (4N) or polyploid (>4N) by a process known as endoreplication [1].…”
Section: To the Editormentioning
confidence: 78%
“…Acute DNA damage by chemotherapeutics would drive terminal differentiation in the stem cells, subsequently causing hair loss. Given that we have found a differentiation response to oncogenic or genotoxic damage in head and neck squamous epithelial cells (Sanz-Gómez et al, 2018), we are tempted to propose a homeostatic role of the DNA damage differentiation response in all squamous epithelia. It is further exciting to speculate that the DNA-damaging sources squamous epithelia are exposed to, such as the UV light of the sun, are at the origin of the stratified epithelia that in turn protect the germinative cell pools.…”
Section: Discussionmentioning
confidence: 93%
“…The implications of these findings are important. We have previously demonstrated that oncogenic or UV irradiationinduced DNA damage or induction of a mitosis block triggers squamous differentiation in keratinocytes of the skin and head and neck in vitro and in vivo (de Pedro et al, 2018;Sanz-Gómez et al, 2018). This response is controlled by mitosis checkpoints and might act as an anti-oncogenic self-protective mechanism (Gandarillas, 2012).…”
Section: Discussionmentioning
confidence: 99%